2023
DOI: 10.3390/ijms24032486
|View full text |Cite
|
Sign up to set email alerts
|

The ANGPTL3-4-8 Axis in Normal Gestation and in Gestational Diabetes, and Its Potential Involvement in Fetal Growth

Abstract: Dyslipidemia in gestational diabetes has been associated with worse perinatal outcomes. The ANGPTL3-4-8 axis regulates lipid metabolism, especially in the transition from fasting to feeding. In this study, we evaluated the response of ANGPTL3, 4, and 8 after the intake of a mixed meal in women with normal glucose tolerance and gestational diabetes, and we assessed their gene expressions in different placental locations. Regarding the circulating levels of ANGPTL3, 4, and 8, we observed an absence of ANGPTL4 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Our data showed that the maternal hepatokines, angiopoietin-like ( Angptl )-4, Angptl-8 , and SelenoP were significantly upregulated while ANgptl-6 was reduced (Figure B). Those hepatokines play crucial roles in lipid metabolism, inflammation, and insulin sensitivity and are essential for the development of the placenta and fetal growth. , Although the information on the relationship of ANGPTLs and placental inflammation is limited, the emerging roles of ANGPTLs in triggering inflammatory signals in multiple tissues have been reported. , In fact, inflammation is known to regulate placental angiogenesis, which is positively associated with the expression of cytokines . While the reduction in the expression of cytokine release from the placenta affects fetal development .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed that the maternal hepatokines, angiopoietin-like ( Angptl )-4, Angptl-8 , and SelenoP were significantly upregulated while ANgptl-6 was reduced (Figure B). Those hepatokines play crucial roles in lipid metabolism, inflammation, and insulin sensitivity and are essential for the development of the placenta and fetal growth. , Although the information on the relationship of ANGPTLs and placental inflammation is limited, the emerging roles of ANGPTLs in triggering inflammatory signals in multiple tissues have been reported. , In fact, inflammation is known to regulate placental angiogenesis, which is positively associated with the expression of cytokines . While the reduction in the expression of cytokine release from the placenta affects fetal development .…”
Section: Resultsmentioning
confidence: 99%
“…Those hepatokines play crucial roles in lipid metabolism, inflammation, and insulin sensitivity and are essential for the development of the placenta and fetal growth. 33 , 34 Although the information on the relationship of ANGPTLs and placental inflammation is limited, the emerging roles of ANGPTLs in triggering inflammatory signals in multiple tissues have been reported. 35 , 36 In fact, inflammation is known to regulate placental angiogenesis, which is positively associated with the expression of cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the expression of FAT and TLR4 in the placenta of GDM patients significantly increases and is positively associated with neonatal weight[ 42 ]. The ANGPTL3-4-8 axis regulates lipid transport and protein expression and is related to fetal birth weight, body length and placental weight[ 43 ]. However, the dysregulated expression of this axis in the placenta of GDM patients has an impact on placental lipid transport and protein expression.…”
Section: Impacts Of Gdm On Placental Transport Functionmentioning
confidence: 99%